Organisation and financing of the health care systems of Bulgaria and Greece - what are the parallels? - Exadaktylos Nikolaos M (BMC, 2005)
Abstract Background The Bulgarian and Greek Medical Care systems have been reformated the last fifteen years. The aim of this study was an examination and comparison of the Bulgarian and Greek Medical Care Systems. Methods This study was prepared by using all the published data related to both Bulgarian and Greek Medical Care systems. Besides, personal communications with related offices such as administration offices of hospitals and Ministries of Health were made. Results In both countries, besides the compulsory insurance there is also additional voluntary insurance which is provided by private companies. The most important difference is the family doctor (specialist in general medicine) existing in Bulgaria. Every insured person needs a 'referral form' completed by the family doctor before visiting a hospital for medical attention (except emergencies). In contrast, in Greece an insured person can directly visit any hospital without needing any forms and independent of the severity of their health problem. An important disadvantage of the Greek health system is the low number of hospitals (139), in relation to population. In contrast, there are 211 hospitals in Bulgaria, although its population is lower than in Greece. Conclusion In both Greek and Bulgarian health systems changes must be done to solve the problems related to informal payments, limited financing, large debts, lack of appropriate investment policy, lack of an objective method for the costing of medical activities and inefficient management.